Policy support for climate-resilient agricultural transformations: IPSR Innovation Profile - Ires, Idil; Jacobs-Mata, Inga (2022)
The policy support program provides governments in East and Southern Africa (ESA) with context-specific recommendations to help improve their enabling environment for climate-resilient agricultural transformation. Specific interests are in sustainable crop intensification and diversification and agribusiness and value chain development, with attention to gender and youth empowerment. The program comprises two pillars: 1) national policy dialogues, which bring together governments, agribusinesses, donors, researchers, and civil society organizations to explore feasible policy and investment interventions, and 2) the ESA Policy Hub, which scales the key takeaways from dialogues to the regional level to tap opportunities arising from trade and regional integration of national economies. Moreover, the program consists of two main innovation bundles: One, the main bundle, is “long-term technical assistance to governments,” garnering results from crosscutting scientific research and national policy dialogues and taking into account climate shocks and stresses to inform policymaking. Two, a “demand-driven technical facility” is available to national actors (government agencies, farmers, and small- and medium-scale enterprises) and connects strategically selected enterprises with a high-impact potential to agribusiness accelerator programs. The program fosters strategic alliances between various innovation partners and works closely with governments to ensure mainstreaming of recommendations into policymaking and implementation.